Local, hypoplastic type of amelogenesis imperfecta: a clinical, genetic, radiological and dermatoglyphic study - (:unkn) unknown (My University, 1996)
A patient and her family members showing X-linked dominant form local, hypoplastic type of amelogenesis imperfecta (AI) were investigated from view-point of their teeth, clinical, genetic, radiological and particularly dermatoglyphic findings. It was suggested that it might be a close relationship between the intra-uterine development of both AI and unusual dermatoglyphs originated from the same layer, ectoderm and an X-linked dominant gene could determine both abnormal teeth and unusual dermatoglyphic characteristics in questions.
Keywords: Humans; Adolescent; Pedigree; Dermatoglyphics; Amelogenesis Imperfecta; Ectoderm; Genetic Linkage; X Chromosome